PENDEKATAN TEORI KONTINGENSI DALAM PERSPEKTIF PENGAMBILAN KEPUTUSAN MANAJEMEN - Wiwi Idawati (Jurnal Akuntansi Bisnis, 2017)
Strict implementation of the budget may depend on such factors, the business strategy that is used and the external environment in which the company operates. Correspondence between contingency factor to the characteristics of budget management should get attention when making decisions to improve the performance of entities. Thus the contingency theory approach plays an important role in management decision-making perspective.Key words : Ketegasan Anggaran, Faktor Kontingen, Keputusan Manajemen.